Analisis Kinerja Keuangan Perusahaan pada Berbagai Sektor Industri di Bursa Efek Indonesia - Esty Apridasari; Atika Lusi Tania; Lella Anita (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This research aims to analyze the comparative financial performance of companies on the Indonesia Stock Exchange in the 2020-2021 period. The population in this study was 750 companies listed on the Indonesian Stock Exchange. The sampling technique in this research used stratified random sampling with 260 companies as sample. The data used in this research was secondary data obtained from financial reports and www.idx.co.id. The results of this research show that in general the sector that has the best financial performance in the period 2020 to 2021 is the healthcare sector, this can be seen from the company's financial ratios which are assessed from the current ratio, debt ratio and return on assets owned by the company in range of research years.